Molecular phenotypes and clinical characterization of familial hereditary breast cancer among half and full sisters - Yingjie Xu; Jun He; Chen Qian; Chengguang Yang (BMC, 2022)
Abstract Background Preliminary clinical observations show that contemporaneous hereditary breast cancer (CHBC) patients suffered breast cancer at an early age, which requires further analysis. Methods 38 familial hereditary breast cancer patients (18 CHBC patients and 20 non-CHBC patients) were screened out and 152 non-hereditary breast cancer patients were used as control subjects. Clinical pathologic subtypes, age, tumor location, histological grade, lymph node metastasis, and molecular phenotype expression (ER, PR, HER-2, Ki-67, CK5/6, E-cad, P63, and P120) were compared across all subgroups. Results The incidence of CHBC was 9.47% (18/190) in breast cancer patients. The average ages of onset of CHBC patients, non-CHBC patients, and non-hereditary breast cancer patients were 49.06 ± 6.42, 60.75 ± 9.95 and 61.69 ± 14.34 respectively; whereas there were no significant differences with respect to pathological type or tumor location. There were significant differences in some histological grading (grade II/III), lymph node metastasis and PR expression between hereditary and non-hereditary breast cancers (P < 0.05; P < 0.05 and P < 0.005, respectively). Significantly different HER-2 expression was observed when comparing all hereditary or CHBC patients with non-hereditary breast cancers (P < 0.05 and P < 0.005, respectively). There were significant differences in E-cad and P63 between contemporaneous hereditary and non-hereditary breast cancers (P < 0.005 and P < 0.05, respectively). Conclusions CHBC patients accounted for 9.47% (18/190) of breast cancer patients, had earlier disease onset, and showed differences compared to non-hereditary breast cancer patients with respect to molecular phenotype and clinical characteristics.